Productivite de bovins N'Dama a la station de Teko (Sierra Leone) et premiers resultats de croisements avec la race Sahiwal - Carew, S.F.; Sandford, J.; Wissocq, Y.J.; Durkin, J.W.; Trail, J.C.M. (1986)
Examines the productivities of N'Dama cattle, introduced Sahiwal cattle, and Sahiwal X N'Dama crossbred at the Teko Livestock Station, Sierra Leone. Evaluates environmental and genetic effects relating to breed group, month and year of parturition or birth, age, sex, individual cow etc. as appropriate for each performance trait.